Legal Review Of The Leakage Due To Misrepresentation Of Local Original Revenue Funds In Tebing Tinggi City In 2025 - Saptha Nugraha Isa; Muhammad Arif Sahlepi; Suci Ramadani (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Tebing Tinggi City Regional Regulation Number 1 of 2024 serves as the basis for collecting Regional Taxes and Regional Levies, including in the entertainment sector. However, the implementation of night market entertainment at Sri Mersing Field showed a significant leakage of Regional Original Revenue (PAD). An investigation by the Anti-Corruption Community Communication (KOMAKI) revealed potential regional losses reaching more than IDR 439 million from the activities that took place from April 22 to June 5, 2025. This loss came from various levies such as food, beverages, parking, entertainment, advertising, and cleaning that were not paid legally, even though they were included as tax objects according to Article 23 and Article 27 of Regional Regulation No. 1 of 2024 concerning Regional Taxes and Regional Levies. Strong suspicions point to systematic tax evasion by legal entity night market organizers (corporations). This violation is not only administrative in nature, but has the potential to become a criminal offense based on Article 102 of Regional Regulation No. 1 of 2024 in conjunction with Article 181 of Law No. 1 of 2022, and can even be qualified as a criminal act of corruption by corporations according to Law No. 31 of 1999 in conjunction with Law No. 20 of 2001. Therefore, the importance of law enforcement for economic crimes that reaches structural aspects, including apparatus accountability and public oversight, is key to preventing systemic neglect in regional governance. This article aims to evaluate the form of violation of the Law on Misappropriation of Regional Original Revenue Funds. Normative legal research with field data shows an element of intent in tax evasion. Therefore, firm legal steps are needed to prevent repeated losses and strengthen the regional government oversight system. This approach is in line with the ideal of Law (Dassolen) to bridge intentionality with empirical reality (Dassein).